The Love of Suffering in “Зеркало (Zerkalo)” by Andrei Tarkovsky - Kirana Chandra Mumpuni Budiana; Hendra Kaprisma; Banggas Limbong (Balai Bahasa Provinsi Riau, 2019)
The topic discussed in this research is the love of suffering in “Зеркало (Zerkalo)” ‘Mirror’ by Andrei Tarkovskiy. This paper is intended to identify the meaning of suffering that is displayed through the character of Maria and background of the place in film. The main theory used in this research is Roland Barthes's semiotic theory, denotation and connotation. The methods that being used in this research are expository, descriptive, and criticism. The result of this research, firstly, the character of Maria in “Зеркало (Zerkalo)” is a masochist figure. The way the Maria confronts suffering is interpreted as a form of страдание (stradanie) 'suffering' that must be enjoyed. The love of suffering is related to the concept of смирение (smirene) 'humility' and судьба (sud'ba) 'destiny' which characterizes masochism in Russia. Secondly, the background of place in this film is illustrated beautifully as if suffering should be glorified.